2011
DOI: 10.1007/s00586-011-2046-5
|View full text |Cite
|
Sign up to set email alerts
|

The impact of halo-gravity traction on curve rigidity and pulmonary function in the treatment of severe and rigid scoliosis and kyphoscoliosis: a clinical study and narrative review of the literature

Abstract: The improvement of pulmonary function and the restoration of sagittal and coronal balance are the main goals in the treatment of severe and rigid scoliosis and kyphoscoliosis. A review of the literature showed that HGT is a useful tool for selected patients. Preoperative HGT is indicated in severe curves with moderate to severe pulmonary compromise. HGT should not be expected to significantly improve severe curves without a prior anterior and/or posterior release. The data presented in this study can be used i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
90
3
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(115 citation statements)
references
References 66 publications
7
90
3
8
Order By: Relevance
“…Kyphoscoliosis is one of the postural deformities caused by abnormal spinal curvature [21]. Truncal mobility is decreased in kyphoscoliosis, which could result in respiratory impairment [21].…”
Section: Upper Camptocormiamentioning
confidence: 99%
“…Kyphoscoliosis is one of the postural deformities caused by abnormal spinal curvature [21]. Truncal mobility is decreased in kyphoscoliosis, which could result in respiratory impairment [21].…”
Section: Upper Camptocormiamentioning
confidence: 99%
“…Severe scoliotic spinal deformities can cause compression of the spinal cord and thoracoabdominal structures [1][2][3], affect the thoracic cage; disturb skeletal, muscular and diaphragmatic function; and reduce respiratory system compliance [24,25]. To date, a series of long-term studies on the natural course of pulmonary impairment and severe scoliosis have shown that there is no spontaneous resolution but rather a slight decline of PFT over time [26], and this is especially the case with curves [100°, in which respiratory system compliance is decreased to levels comparable to those of adult respiratory distress syndrome, which lead to patients suffering long-term sequelae.…”
Section: Discussionmentioning
confidence: 99%
“…However, the results of other experiments were significantly different and sometimes contradictory. Heiko et al [24] showed that pre-op-HGT did not induce a meaningful release effect for rigid curves, and that the difference in flexibility between HGT radiographs and bending or traction radiographs was not significant. In studies by Seller [54] and Flierl [55], HGT did not improve surgical outcomes for scoliosis.…”
Section: Discussionmentioning
confidence: 99%
“…Halo-related complications, such as pin-site infection and loosening, and neurological damage, have been encountered. A recent review of the literature has reported a rate of 53%, with 10% requiring surgery and 31% suffering from transient halo-related neurologic compromise [16,17]. In other series, a 31% incidence of complications can be found, including cranial nerve injuries, Horner syndrome, extremity weakness and bradycardia [3].…”
Section: Halo Tractionmentioning
confidence: 99%